The Effect of Participative Learning Strategy and Interpersonal Communication on Results of Civic Learning Education - Robinson Hutagaol; Abdul Hasan Saragih; Sahat Siagian (Britain International for Academic Research (BIAR) Publisher, 2020)
The purpose of this study is to determine the differences in civic learning outcomes of students who are taught with participatory group and individual learning strategies, know the differences in civic learning outcomes that have high interpersonal communication and who have low interpersonal communication and know the interactions between learning strategies and interpersonal communication learning outcomes of Civics. To test the hypothesis the learning outcomes used are civic learning outcomes that have high interpersonal communication and learning outcomes that have low interpersonal communication. The statistical test used in this research descriptive statistics presents the statistical data used by ANAVA, the data analyst requirements test, namely the normality test, the lilifors and the Variance homogeneity test with the Bartlett test. The research instrument of civic learning outcomes using a multiple choice test consists of 35 items and has a reliability of 0.761 using the Kuder-Richardson formula (KR-20). For students who have high and low interpersonal communication using interpersonal communication tests using a standard Likert scale. The results of hypothesis testing show that being taught with a participatory group strategy has a higher PKn learning outcome than the individual participatory strategy learning outcomes. This is indicated by the count = 1.20> table = 4.02, at the significance level α = 0.05. High interpersonal communication higher Civics learning outcomes that have low interpersonal communication. This is indicated by F arithmetic = 48.46> table = 4.06 on Significant level α = 0.05 with dk = (1.76), and the interaction between learning strategies and students' interpersonal communication towards learning outcomes of Civics. This shows the count = 48.46> table = 4.06 at a significant level α = 0.05.